Perspektif Orang Tua terhadap Urgensi Pendidikan Formal Usia Dini di Kp. Pangkalan Desa Segarajaya - Mista, Hunaidah; Sari, Atika Sukma; Sari, Dwi Chyntia; Fazrin, Siti Zulaikha; Rahmah, Syafiyah Nur’aini (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine parents' overall views on the importance of formal early childhood education in Kp Pangkalan, Segarajaya Village, Tarumajaya District, and how families assess the significance of early childhood education for children in their sensitive phase. Early childhood has brain cells that need to be stimulated. They are the nation's superior generation and are going through a very vital period that will influence their future. This descriptive study adopts a quantitative approach. The participants in this study were parents living in KP Pangkalan. Information for the research was collected through a questionnaire consisting of ten questions distributed to 23 respondents. The research findings indicate that parents' views on the importance of early childhood formal education in Kp Pangkalan, Segarajaya Village are at the